Особливості та труднощі перекладання наукових текстів - Мухачова, О. В. (ХНУРЕ, 2019)
This article tells about standards of translating science and technical articles and analyzes its difficulties and distinctive features. Also it describes the ways of translating terms in science and technologic articles.